Disentangling ADHD's Presentation-Related Decision-Making—A Meta-Analytic Approach on Predominant Presentations - Schulze, Marcel; Coghill, David; Lux, Silke; Philipsen, Alexandra (Frontiers in Psychiatry, 2021)
Background: Deficient decision making (DM) in attention deficit/hyperactivity disorder (ADHD) is marked by altered reward sensitivity, higher risk taking and aberrant reinforcement learning. Previous meta-analysis aggregate findings for the ADHD combined presentation (ADHD-C) mostly, while the ADHD predominantly inattentive presentation (ADHD-I) and the predominantly hyperactive/impulsive presentation (ADHD-H) were not disentangled. The objectives of the current meta-analysis were to aggregate findings from DM for each presentation separately. Methods: A comprehensive literature search of the PubMed (Medline) and Web of Science Database took place using the keywords ‘ADHD’, ‘attention-deficit/hyperactivity disorder, ‘decision making’, ‘risk-taking’, ‘reinforcement learning’, and ‘risky’. Random-effects models based on correlational effect-sizes were conducted. Heterogeneity analysis, sensitivity/outlier analysis were performed and publication bias were assessed with funnel plots and egger intercept. Results: Of 1240 candidate articles, 7 fulfilled criteria for analysis of ADHD-C (N=193), 7 for ADHD-I (N=256) and 8 for ADHD-H (N=231). Moderate effect-size were found for ADHD-C (r=0.34; p=.0001; 95% CI=[0.19, 0.49]). Small effect-sizes were found for ADHD-I (r=0.09; p=.0001; 95% CI = [.008, .25]) and for ADHD-H (r=0.1; p=.0001; 95% CI = [-.012, 0.32]). Heterogeneity was moderate for ADHD-H. Sensitivity-analysis show robustness of the analysis and no outlier was detected. No publication bias was evident. Conclusion: This is the first study that uses a meta-analytic approach to investigate the relationship between the different presentations of ADHD separately. These finding provide first evidence of lesser pronounced impairment in DM for ADHD-I and ADHD-I compared to ADHD-C. While the exact factors remain elusive, the current study can be considered as a starting point to reveal the relationship of ADHD presentations and DM more detailed.